Crime and Illegal Work - (:unkn) unknown (My University, 2019)
Many expressions in African societies identify groups that operate between the legal and illegal at the frontier of petty and serious crime: tsotsis or skollies in South Africa; wahuni in Tanzania; jaguda boys, boma boys or area boys in Nigeria. They designate broad categories that embrace the criminal, the delinquent, the young and the jobless. For a large section of society, these common labels represent the embodiment of danger, disorder, crime and delinquency. To consider an unemployed young person and a leader of a gang as belonging to the same category shows the difficulty in disentangling joblessness and crime...
Keywords: African Research